Joint dynamics and intra-subject variability during countermovement jumps in children and adults - Raffalt, Peter C.; Alkjær, Tine; Simonsen, Erik B. (Journal of biomechanics, 2016)
The present study investigated lower limb joint work, lower limb joint energy transport and intra-subject variation of the joint dynamics during countermovement jumps in children and adults. Twelve healthy men and eleven healthy boys performed ten maximal countermovement jumps. Three dimensional kinematics and kinetics were recorded in synchrony. Hip, knee and ankle joint eccentric and concentric work, joint energy transfer, intra-subject variation of joint moment, joint power and joint moment components were calculated. The children had lower eccentric and concentric hip work and lower eccentric knee work but no group difference was observed in the concentric knee joint work and ankle joint work. Eccentric hip and knee joint energy transfer and concentric hip joint energy transfer were higher in adults. The children had higher intra-subject variation in the eccentric and concentric hip joint work, hip joint moment and hip and knee joint power. Higher intra-subject variation was observed in horizontal joint reaction force components for the children and higher intra-subject variation in the segment angular inertia components was observed for the adults. The joint dynamics of children during countermovement jumps were less efficient in producing proximal joint work, transferring energy through joint centres and characterized by a higher intra-subject variation.